Insulamento burocrático, autonomia do Estado e inserção social: um estudo do Ministério da Saúde na coordenação nacional do SUS - Luciana Assis Costa (2011)
This thesis has as its objective of analysis the structure of the state apparatus responsible for the formulation and coordination of the politics of healthcare after 1990, starting with the configuration of the bureaucracy of the Ministry of Health and its connections with the societal forces involved in this topic. The analytical argument that permeated the study is that which is not the excess of public bureaucracy because of inefficiencies in the State conduct of sectoral policies, but rather the lack of a cohesive and meritocratic administrative frame articulated with societal forces engaged in the sector. The study reveals that the federalmanagement of SUS (National Health System) was developed by an extremely vulnerable administrative frame, through analysis of both the recruitment model of the servants of the Ministry of Health headquarters as well as the processes of internal promotion in the sector. The absence, and not the excess, of a Weberian bureaucracy in the sphere of the Ministry of Health was determined as one of the gravest problems in the national c oordination of healthcare policy. Nonetheless, healthcare policy is still recognized nationally, after the consolidation of National Health System - SUS, as one of the most successful social policies.Without disregarding the deadlocks that the system confronts, the indications of healthcare since 1990 show a significant improvement in the condition of access and quality of the services provided to the Brazilian population. The advances in healthcare policy can partiallybe explained by the presence of organizational and cultural mechanisms that contributed towards forging a balance between the insulation of the bureaucracy of the Ministry of Health and its societal insertion. This analysis is supported by the model of embedded autonomy theorized by Peter Evans, based in the on comparative institutional approach, which expands upon the closed model of rationality, to treat the State not as isolated from the environment, but as sensitive to the surrounding social relations. The study was conducted starting with a qualitative inquiry, in which the techniques of data collection were basically the analysis ofprimary sources (federal laws, selected ministerial edicts and norms, official documents of the Ministry of Health) and semi-structured interviews with healthcare specialists. The work was developed and structured into four chapters. The first chapter refers to theoretical grounding, discussing the possibility of analysis of the relationship between the state and society, beginning with sociological institutionalism under the viewpoint of the model of embedded autonomy suggested by Peter Evans coupled with the concept of isomorphism by DiMaggio and Powell. The second chapter is a historical synthesis of the consolidation of the Brazilian healthcare system, emphasizing the duality of healthcare policy until 1990 and thereafter the consolidation of SUS under the coordination of the Ministry of Health. The third chapter seeks to set the formal structure of the Ministry of Health beginning with the recruitment model of the servants and career plans. In closing, the fourth chapter identifies the administrative web of healthcare, represented by the concrete channels of participation in the federal circuit, qualifying the relationship between the Ministry of Health and these mechanisms in the conveyance of policy